2016
DOI: 10.1103/physrevb.93.024417
|View full text |Cite
|
Sign up to set email alerts
|

Complex magnetic phase diagram and skyrmion lifetime in an ultrathin film from atomistic simulations

Abstract: We determined the magnetic B − T phase diagram of PdFe bilayer on Ir(111) surface by performing Monte Carlo and spin dynamics simulations based on an effective classical spin model. The parameters of the spin model were determined by ab initio methods. At low temperatures we found three types of ordered phases, while at higher temperatures, below the completely disordered paramagnetic phase, a large region of the phase diagram is associated with a fluctuation-disordered phase. Within the applied model, this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
2
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 75 publications
9
74
2
4
Order By: Relevance
“…Moreover, it is known that the exchange coupling of Fe could be both ferromagnetic and antiferromagnetic which depends on the substrates' d-band filling. [42][43][44] Recently, ab initio calculation showed that ferromagnetic NN and AFM NNN interaction could coexist in multilayer Pt 1−x Ir x / Fe/Pd structures, 45 where our simulation results are promising and remain to be verified experimentally.…”
Section: B Hysteresis Loopmentioning
confidence: 73%
“…Moreover, it is known that the exchange coupling of Fe could be both ferromagnetic and antiferromagnetic which depends on the substrates' d-band filling. [42][43][44] Recently, ab initio calculation showed that ferromagnetic NN and AFM NNN interaction could coexist in multilayer Pt 1−x Ir x / Fe/Pd structures, 45 where our simulation results are promising and remain to be verified experimentally.…”
Section: B Hysteresis Loopmentioning
confidence: 73%
“…Skyrmions are also present in Fe (ultra-)thin-films, e.g., Fe monolayer on Ir(111) [20], Pd/Fe bilayer on Ir(111) [9,10,[30][31][32], 3 monolayers of Fe on Ir(111) [33] and Co ultrathin film Co/Ru(0001) [34]. In that case, magnetic interactions can be tuned by the choice of the magnetic film [35,36], the hybridization with the different substrates [11,35,37,38], or optional overlayers [9].…”
Section: Introductionmentioning
confidence: 99%
“…The question then arises as to how general this relation between skyrmion size and skyrmion stability is and whether it is possible to design an optimal medium where magnetic skyrmions are small enough while being sufficiently stable at ambient conditions. Equilibrium properties of skyrmions such as size and shape have intensively been studied since the very discovery of magnetic skyrmions more than twenty years ago [2][3][4][22][23][24][25][26], but quantitative characterization of skyrmion stability has started being addressed rather recently [27][28][29][30][31][32][33][34][35][36][37][38]. Thermal stability can be quantified by calculating skyrmion lifetime using harmonic transition state theory for spins [39].…”
Section: Introductionmentioning
confidence: 99%